Enhanced photoelectrochemical properties of hierarchical black TiO2-x nanolaces for Cr (VI) photocatalytic reduction. (3rd September 2020) - Chahrour, Khaled M.; Yam, F.K.; Eid, A.M.; Nazeer, Ahmed Abdel
Abstract: In this work, hierarchical TiO2 nanolace (NL-TiO2 ) films have been synthesized by a two-step anodization technique. This was followed by a reduction in a hydrogen atmosphere to prepare the reduced black version of such hierarchical nanolaces (NL-TiO2-x ). The FESEM images confirmed highly-ordered nanolace arrays structure for all the synthesized films. The Ti 3+ ions/oxygen vacancies were confirmed using XPS spectra. The photoelectrochemical properties of NL-TiO2-x showed superior character in comparison with NL-TiO2 by the virtue of the promoted electron-hole separation efficiency, which induced by the Ti 3+ ions/oxygen vacancies in NL-TiO2-x . The data showed that the NL-TiO2-x film annealed at 650 °C attained the maximum photoelectrochemical properties with a significant ABPE and IPCE of 0.58% and 52.51%, respectively. The applied photocatalytic reduction of Cr (VI) as an environmental contaminant to Cr (III) was effectively done using NL-TiO2-x and NL-TiO2 annealed at 650 °C with a photocatalytic reduction rate 48.15% and 27.5%, respectively. Highlights: NL-TiO 2 hierarchical nanolaces were synthesized by two-step anodization technique. Hydrogenated NL-TiO 2-x nanolaces were fabricated using a H2 /N2 reducing atmosphere. Superiority of NL-TiO 2-x at 650 °C was due to Ti 3+ self-doping and bi-phased synergy. NL-TiO 2-x annealed at 650 °C had higher rate of Cr(VI) reduction to Cr(III). Warburg impedance appeared for NL-TiO 2-x due to the anomalous diffusion character.